Mekanisme Transaksi Gadai Perspektif Hukum Ekonomi Syari’ah - Syaripudin, Enceng Iip; Nurul Mustofa , Annisa (Jurnal Hukum Ekonomi Syariah, 2022)
Islam regulates various aspects of human life (muamalah), including pawn transactions. In conducting muamalah, pawning is not uncommon among Muslim communities, yet there are still practices that contradict Shariah economic law. The formulation of the problem in this research is: What is the mechanism of pawn transactions in Kp. Karoya, Cibatu Sub-District, Garut Regency? What is the perspective of Shariah economic law on the mechanism of pawn transactions? The objective of this research is to analyze the mechanism of pawn transactions in Kp. Karoya, Cibatu Sub-District, Garut Regency, and then analyze the perspective of Shariah economic law on the pawn mechanism in Kp. Karoya. The research method used is field research and a qualitative approach. The results of the research on the pawn mechanism reveal several aspects that contradict Shariah economic law, namely: 1) There is no written evidence during the contract, which contradicts both Quranic verses and Hadith. 2) Uncertainty regarding the end date of the pawn transaction, where if the redemption period expires, there should be another deadline for the transaction. 3) The use of pawned items not listed in the transaction, although this may be customary and does not contradict Shariah economic law. Keywords: Transactions, Pawn, Shariah Economic Law